2008
DOI: 10.1093/brain/awn278
|View full text |Cite
|
Sign up to set email alerts
|

Strongly reduced volumes of putamen and thalamus in Alzheimer's disease: an MRI study

Abstract: Atrophy is regarded a sensitive marker of neurodegenerative pathology. In addition to confirming the well-known presence of decreased global grey matter and hippocampal volumes in Alzheimer's disease, this study investigated whether deep grey matter structure also suffer degeneration in Alzheimer's disease, and whether such degeneration is associated with cognitive deterioration. In this cross-sectional correlation study, two groups were compared on volumes of seven subcortical regions: 70 memory complainers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

49
330
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(382 citation statements)
references
References 36 publications
49
330
3
Order By: Relevance
“…Only recently, the latter have been identified as regions with a high susceptibility for AD pathology. 25 Our findings of a progressive MTR reduction in the basal ganglia and thalamus are in line with the observation of a significant atrophy of the putamen and thalamus in AD. 25 We would also have expected to find MTR reductions in the cortex.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Only recently, the latter have been identified as regions with a high susceptibility for AD pathology. 25 Our findings of a progressive MTR reduction in the basal ganglia and thalamus are in line with the observation of a significant atrophy of the putamen and thalamus in AD. 25 We would also have expected to find MTR reductions in the cortex.…”
Section: Discussionsupporting
confidence: 90%
“…25 Our findings of a progressive MTR reduction in the basal ganglia and thalamus are in line with the observation of a significant atrophy of the putamen and thalamus in AD. 25 We would also have expected to find MTR reductions in the cortex. 16,26 However, due to limited image resolution and partial volume effects, we unfortunately were not able to obtain reliable and reproducible MTR values in the cortex, and therefore abstained from such analysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The diffuse projections of these subcortical structures may account for the wide range of cognitive findings and cortical damage exhibited across the C9ORF72 mutation cohort here. Involvement of thalamus and cerebellar connections could underpin the prominent neuropsychiatric features shown by these cases (Andreasen et al, 1996;Schmahmann, 2005;Goossens et al, 2007;Straube et al, 2007;Schmahmann and Pandya, 2008;Tedesco et al, 2011), as well as episodic memory deficits ( Van der Werf et al, 2003;de Jong et al, 2008) somatic complaints, hallucinations and delusions (Kessler et al, 2009;Tedesco et al, 2011). Although none of our cases had frank cerebellar ataxia, this has been described in previous cases of chromosome 9 linked FTLD (Pearson et al, 2011).…”
Section: Discussionsupporting
confidence: 67%
“…Volumetric loss in the thalamus has been proposed as a predictor of dementia, 46 while studies have demonstrated thalamic atrophy in PD with dementia compared with healthy individuals. 14,16 Previous studies have also demonstrated the relation of thalamic atrophy to cognitive performance in other neurologic disorders, including Alzheimer disease, 47 Huntington disease, 48 and multiple sclerosis. 49 Considered in light of those findings, the volumetric reduction of the thalamus observed in our PD-MCI group may reflect an intermediary stage of cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%